Depressive Disorders in Children and Adolescents: What Every School Counselor Needs to Know. Issue 1 (1st January 2016) - Dugger, Suzanne M.; Jones, Kalinda R.
Abstract : This article addresses the role of school counselors in recognizing and responding to students with depressive disorders. It provides an overview of depressive symptoms, including how these symptoms tend to be displayed by children and adolescents, before describing three evidence-based intervention approaches. The article concludes with an exploration of specific ways in which school counselors can address depressive disorders within the context of the ASCA National Model.